Pengaruh Model Problem Based Learning Berbantuan Mind Mapping terhadap Kemampuan Berpikir Kritis Siswa pada Materi Sistem Pencernaan - Dewi Ribreka Br Bangun; Syahmi Edi (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Critical thinking skills are essential competencies that need to be developed in biology learning to help students analyze and solve problems logically. However, students’ critical thinking skills are still relatively low, indicating the need for learning models that can enhance student engagement and understanding. This study aimed to determine the effect of the Problem-Based Learning model assisted by mind mapping on students’ critical thinking skills in the digestive system topic among Grade XI students at SMA Negeri 12 Medan. This research employed a quasi-experimental method using a pretest-posttest nonequivalent control group design. The sample consisted of an experimental class taught using the Problem-Based Learning model assisted by mind mapping and a control class taught using the Problem-Based Learning model only. Data were collected through critical thinking tests administered as pretests and posttests and were analyzed using the Independent Sample t-test. The results showed that the mean score of the experimental class increased from 48.03 to 75.61, while the control class obtained a posttest mean score of 71.78. Data analysis revealed a significance value of 0.015 < 0.05, indicating a significant effect on students’ critical thinking skills. This study contributes to the development of innovative learning models to improve students’ critical thinking skills in biology learning.